Quantification of the running demands in women`s field hockey using individualized thresholds - Ortega-Gálvez, M. J.; Cabezas-Ramos, D.; Gálvez-González, J. (Revista Internacional de Ciencias del Deporte, 2019)
The objective of this study was to analyze the running demands of women`s field hockey, using relative values to determine intensity thresholds. 15 players (23,7 ± 4,1 years) were monitored in official competition matches, using a global positioning system (GPS). To determine the thresholds relative to the intensity of the race, the 30-15IFT test and the maximum sprint speed were used. The results show that there are significant differences between the analysis of high-speed running of the hockey players with absolute and relative values, increasing from 479.8 ± 134,9 m to 1116,3 ± 281,4 m; Effect size ± 90% CL = 2,78 (2,17-3,38), distances that are more accurate to the player`s effort. However, the sprint number was decreased (from 6,26 to 3,59). The use of relative thresholds increases high-intensity running in women`s field hockey.